Effect of bioelectrical impedance analysis-guided dry weight adjustment, in comparison to standard clinical-guided, on the sleep quality of chronic haemodialysis patients (BEDTIME study): A randomised controlled trial - Sethanant Sethakarun (2020)
© 2019 The Author(s). Background: Sleep disturbance is common among chronic haemodialysis patients, which leads to poor quality of life, in addition to increased instances of morbidity and mortality. Hypervolemia has been linked to sleep problems observed in chronic haemodialysis patients, which suggests that optimising one's fluid status could improve the sleep quality of this patient group. In our study, we subjectively examined and objectively measured sleep parameters, using actigraphy recordings, the Pittsburgh Sleep Quality Index (PSQI) questionnaire, and Epworth Sleepiness Scale (ESS), in order to compare bioelectrical impedance analysis (BIA)-guided and standard clinical-guided dry weight adjustment. Methods: We randomly selected 19 chronic haemodialysis patients with subclinical hypervolemia, defined as a clinically euvolemic status, despite the ratio of extracellular water to total body water being more than 0.4 in BIA. Furthermore, these patients, who were poor sleepers (PSQI > 5), were assigned to either a BIA-guided dry weight group (BIA group) or a standard clinical-guided one (clinical group). The primary outcome was changes in sleep actigraphy parameters between the groups at 1, 3, and 6 months. Changes observed in the PSQI and ESS score between the two groups over the same period of time were the secondary endpoints. Results: The mean age of the participants was 63.53 ± 11.12 years, and 42% of them were male. All sleep parameters measured by means of actigraphy were not significantly different between the two groups. Interestingly, at 3 and 6 months, the subjective sleep quality significantly improved in the BIA group, as reflected by a greater decline in the PSQI score, in comparison with the clinical group (3 months: mean difference - 1.82 [- 3.13 to - 0.51], P = 0.006; 6 months: mean difference - 3.16 [- 4.49 to - 1.83], P < 0.001). However, sleepiness assessed by the ESS was not significantly different between the groups throughout the study. Conclusions: Optimisation of the fluid status by employing BIA did not improves sleep actigraphy parameter, however, it significantly ameliorates the subjective sleep quality of chronic haemodialysis patients. This observation should be further explored in larger samples and longer clinical trials. Trial registration: This trial was registered at ClinicalTrials.gov (NCT02825589) on July 7, 2016.